Assessment of Major Diseases and Insect Pests of Horticultural Crops in Eastern Amhara, Ethiopia - Mihretie, Aderajew; Kassaw, Admasie; Gashaw, Berhan; Yimer, Desalegn; Ayalew, Abebe; Mihretie, Akalu (Department of Agronomy and Horticulture, IPB University, 2026)
Diseases and insect pests are serious problems affecting horticultural crops grown in mid and lowland areas. A systematic survey was conducted to assess the distribution, incidence, and severity/damage levels of diseases and insect pests of horticultural crops in the mid- and lowland areas of the North and South Wollo zones (Kalu, Tehuledere, Habru, and Kobo districts) during the 2017/2018 main and irrigation seasons. During the survey, a total of 279 fields on 14 different horticultural crop types were addressed. As revealed by the assessment, horticultural crops are subjected to numerous pests. Citrus woolly whitefly (Aleurothrixus floccosus) and leaf miner (Phyllocnistis citrella) on citrus; fruit flies (Thepritidea species) on coffee; diamondback moth (Plutella xylostella) on cabbage; and thrips on onion were the most destructive insect pests in the area. Especially, woolly whitefly in Kobo and leaf miner in Kalu districts were the major pests of citrus, with severities of 38.97% and 31.84%, respectively. Regardless of location, leaf miner was the most severe pest (42.31%) at the seedling stage of citrus. whereas, anthracnose (Colletotrichum species) and powdery mildew (Oidium caricae) on mango, anthracnose on avocado, purple blotch (Alternaria porri) on onion, and black sigatoka (Pseudocercospora fijiensis) on banana were found to be the major diseases in their order of damage level and occurrence. This clearly indicates the need for regular and targeted pest monitoring on the one hand and the development of management options for the most important horticultural crop pests of the area on the other.